Bodies, Booze, and Bros: an Ethnographic Study of Masculinity at Las Vegas Beach and Day Clubs - Christopher (Masculinities and Social Change)
Beach and Day Clubs are popular alternatives to traditional nightclubs, as events occur in the daytime with the body on full display in swim attire. My research provides a significant contribution to the literature in masculinity due to the difficulty in gaining insider status to Las Vegas Beach and Day Clubs specifically. Drawing from participant observation and interviews over a six-year period, the findings reveal how they are a unique site of masculinity construction for men through the body, both outside and inside the venue. They also serve as places to reproduce gendered hierarchies and masculinities. The results additionally highlight the importance of homosociality and girl hunting in understanding group interaction among men, and the implications they have on those in these leisure spaces.